Experimental investigation on the effect of steel fiber embedded in marble dust based concrete. (2020) - Shukla, Ashish; Gupta, Nakul; Kishore, Kamal
Abstract: In the modern era, concrete is considered as synonymous with strength and durability. The application of cement and production causes the reason for pollution in the environment. To mitigate such problems, industrial waste are frequently utilized in the concrete construction as a partial replacement of cement, reducing carbon footprint in the atmosphere and leading to enhanced strength. In this study, M20 grade concrete with marble dust in 0%, 5%, 10%, 15% and 20% in proportion along with ratios of steel wires were used and tested for 7 & 28 days on mechanical parameters. The study reveals that the inclusion of 1% steel fiber and 15% replacement of marble dust with cement exhibiting the highest mechanical strength over the ordinary concrete and other proportions. Moreover, beyond this fraction, reduction in strength is greatly achieved. As results revealed, adding certain fixed amount of marble dust with steel fiber have improved and dense interlock aggregate particles, resulting in more durable over the ordinary cement concrete.